Pengenalan Permainan Bulutangkis pada Usia Sekolah Dasar - Komari, Amat (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
Badminton game socialization is very needed on elementary school age childrenbecause it is suitable with condition of elementary school age children posture. One ofthose adjustments is a tool of game used is relatively light in accordance with muscularcapacity of elementary school children. To improve children’s independency in orderthat is expected, it needs to give an interesting extrinsic motivation to do badmintonactivity.In presenting game material, it is better to adjust with skill of students so that it stillneeds to add movements enrichment (multi lateral skill) that function to completemovement memories in their brain screen. If this movement memory is taken out atany time, it is useful for children to ease learning new movements and to do addedmovement in rescuing themselves from possibility injured. In order that children donot bored fastly, presentation method uses playing approach. Therefore in foreplay itis chosen playing activity that can increase temperature of body to prepare physicaland psychological condition before running heavier activities.Types of introduction through games lead to badminton activity are, for example, byshot ball, and head throwing by shuttlecock. Although badminton has been competedon early age, the important thing through this game competition is students can addexperiences to recognize their environment more, look playing-schedule, prepare eatand drink time, prepare clothes, shoes and choose transportation means in order notcoming late. Besides that, they can learn accepting defeat, conceding strength of otherpeople and gaining social-interaction experiences not given at school. The materialpresented consists of many varieties of foreplay, running variation, individual gymnastics, in pair gymnastics, games, kinds of raket-handling, overhead stroke posture,lob, dropshot and smash stroke also foot-movement doing.Keywords: Badminton, Early Age, Socialization